Cable networks, services and management - Toy, Mehmet (Hoboken : IEEE / Wiley, 2015)
"This book will focus on residential and commercial services provided by MSOs (Multiple System Operators), the networks supporting these services, and management of networks and services. The book will cover current technologies used by MSOs and future directions pointing out areas requiring further research"--
3.6.1 CMTS and CCAP Performance Metrics Collection3.6.2 CM Performance Metric Collection; 3.7 BILLING SYSTEMS AND FORMATS; 3.7.1 Downstream Interfaces; 3.7.2 Upstream Interfaces; 3.7.3 Billing; 3.7.4 Product Catalog; 3.8 SECURITY; 3.8.1 Security in DOCSIS 3.0/3.1; 3.8.2 PacketCable Security; 3.9 CONCLUSION; REFERENCES; CHAPTER 4 BUSINESS NETWORK ARCHITECTURES AND SERVICES; 4.1 INTRODUCTION; 4.2 METRO ETHERNET ARCHITECTURE AND SERVICES; 4.2.1 Architecture; 4.2.2 ETH Layer Characteristic Information (Ethernet Frame); 4.2.3 User-to-Network Interface; 4.2.4 Ethernet Virtual Connection.
Includes bibliographical references.
Print version record and CIP data provided by publisher.
Keywords: Integrated services digital networks; Internet service providers -- Management; Home computer networks; Cable television; Cable television; Home computer networks; Integrated services digital networks; Internet service providers -- Management; TECHNOLOGY & ENGINEERING -- Telecommunications; Electronic books; Electronic books